Vietnam - Stads, Gert-Jan; Nguyen, Pham Thi; Suu, Tran Danh; Nin-Pratt, Alejandro; Xuan, Pham Thi; Omot, Norah; Bo, Nguyen Van (International Food Policy Research Institute, 2020)
Agricultural research spending in Vietnam has increased steadily since 2000. Nonetheless, as of 2017, Vietnam only invested 0.20 percent of its AgGDP in agricultural research, which is insufficient to address the multitude of challenges the agricultural sector is facing. The country has made considerable progress in building its agricultural research capacity. Average degree levels of scientists have improved markedly over time. Recent growth in agricultural research spending and staffing is likely to be reversed in the coming years because the Vietnamese government plans to reduce public research staffing and take steps to stimulate private research and funding.